Strategi Kepala Sekolah dalam Meningkatkan Kinerja Guru Di SMAN 10 Tasikmalaya - Yonandi, Yonandi (Jurnal Inovasi dan Teknologi Pendidikan, 2022)
This research was motivated by the lack of the principal's strategy in improving teacher performance at SMAN 10 Tasikmalaya. The purpose of this study was to determine the description of the principal's strategy, supporting factors and obstacles to the principal's strategy in improving teacher performance at SMAN 10 Tasikmalaya. This research approach is qualitative with a descriptive type of approach. This research was conducted at SMAN 10 Tasikmalaya. The data sources in this study are school principals and teachers representing scientific clusters. Data collection techniques in the form of observation, interviews, and documentation. Data analysis techniques use data reduction, data presentation, and conclusion drawing. Checking the validity of the data using trianggulation techniques. The results showed that the principal's strategy in improving teacher performance at SMAN 10 Tasikmalaya includes: (1) Learning planning, the strategies used include coaching teacher performance, through MGMP activities, including participating in training. (2) Implementation of learning, the strategies used include supervision / supervision of classroom management, facilitating learning media facilities, giving teachers flexibility in the use of learning methods, providing motivation, giving awards. (3) Evaluation of learning, the strategies used include providing facilities and controlling the implementation of learning evaluation. The supporting factors include, with the availability of various rpp making tools, especially guidelines for compiling rpp, as well as learning evaluation equipment facilities, especially assessment formats, student enthusiasm in participating in learning, and learning media facilities provided at SMAN 10 Tasikmalaya are quite adequate. Meanwhile, the inhibiting factors include difficulty adjusting between what is in the rpp with real conditions, some students do not follow BDR due to network constraints, and the IT skills of some teachers are inadequate